The Paradigm of G Protein Receptor Transactivation: A Mechanistic Definition and Novel Example - Peter J. Little; Micah L. Burch; Sefaa Al-aryahi; Wenhua Zheng (The Scientific World Journal)
Seven transmembrane G protein—coupled receptors are among the most common in biology and they transduce cellular signals from a plethora of hormones. As well as their own well-characterized signaling pathways, they can also transactivate tyrosine kinase growth factor receptors to greatly expand their own cellular repertoire of responses. Recent data in vascular smooth muscle cells have expanded the breadth of transactivation to include serine/threonine kinase receptors, specifically the receptor for transforming growth factor beta (TGF-β). Stimulation with endothelin and thrombin leads to the rapid formation of C-terminal phosphorylated Smad2, which is the immediate product of activation of the TGF-β receptor. Additionally, it appears that no definition of transactivation based on mechanism is available, so we have provided a definition involving temporal aspects and the absence of de novo protein synthesis. The phenomenon of transactivation is an important biochemical mechanism and potential drug target in multiple diseases.